The bilateral J-curve between Ghana and her key trading partners - Benedict Arthur; Afenya Millicent Selase; Michael Asiedu; Rebecca Aduku (Cogent Economics & Finance, 2022)
This study examines the J-Curve phenomenon of a developing country for the case of Ghana and its major trade partners: Switzerland (Swiss) and China. Using quarterly bilateral data from Q1-1995 to Q4-2018 to investigate the impact of currency depreciation on the bilateral trade balance in the short and the long run, it was established that the depreciation of Ghana Cedis in recent years could be considered as a successful policy for the trade balance improvement of Ghana. First, the real depreciation of Ghana Cedis improves Ghana's trade balance with China and the Swiss after worsening the trade balance in the short run. Second, in the long run, the Ghana trade balance is improved from a real depreciation of Cedis, which formed 3.235 percent and 1.594 percent of Ghana's total trade share with China and Swiss, respectively. Third, the estimates show evidence of the J-Curve phenomenon only in the cases of China, not for the Swiss. Additionally, the real income of trading partners has a positive and significant effect in the long run, indicating that an increase in the real income of partners has an important role in determining imports from Ghana. However, there is no significant effect on Ghana's real income on the trade balance. Lastly, the results from diagnostic tests show that the estimated relationships have been stable and reliable over the last 24 years. Consequently, in line with the study results, the authors recommend several policy implications to improve the trade balance in Ghana.
Keywords: F13; F14; F31; B27; 330; J-Curve phenomenon; bilateral trade balance; real exchange rate; ARDLapproach; Ghana